2019
DOI: 10.1302/0301-620x.101b2.bjj-2018-0754.r1
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar fusion involving the sacrum increases dislocation risk in primary total hip arthroplasty

Abstract: AimsConcurrent hip and spine pathologies can alter the biomechanics of spinopelvic mobility in primary total hip arthroplasty (THA). This study examines how differences in pelvic orientation of patients with spine fusions can increase the risk of dislocation risk after THA.Patients and MethodsWe identified 84 patients (97 THAs) between 1998 and 2015 who had undergone spinal fusion prior to primary THA. Patients were stratified into three groups depending on the length of lumbar fusion and whether or not the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 29 publications
1
73
0
Order By: Relevance
“…Recent literature has reported the postural changes from standing to sitting, which can tremendously affect the stability of total hip arthroplasty (THA) [1][2][3][4][5][6]. The pelvis kinematics in standing to sitting transition is commonly considered as a rotation around the axis that connects the center of the 2 femoral heads (hip axis).…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has reported the postural changes from standing to sitting, which can tremendously affect the stability of total hip arthroplasty (THA) [1][2][3][4][5][6]. The pelvis kinematics in standing to sitting transition is commonly considered as a rotation around the axis that connects the center of the 2 femoral heads (hip axis).…”
Section: Introductionmentioning
confidence: 99%
“…Dislocation remains one of the most common early complications after posterolateral primary THA [1][2][3]16]. There is growing evidence that patients who underwent spinal fusion are at the highest risk for postoperative dislocation, with some reports of up to a 10% dislocation rate [4][5][6][7][8][9][10][11][12][13][14]. The spinopelvic immobility in these patients can lead to bony impingement, causing postoperative instability [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, high-risk patients with prior spinal fusions undergoing primary posterolateral THA with a DM construct did not experience any dislocations at a mean of 3 years of follow-up (range, 1-7 years). There is growing evidence that this patient population is at significant risk of postoperative dislocation [4][5][6][7][8][9][10][11][12][13][14]. In a matched propensity study, Perfetti et al [6] reported a sevenfold increased rate of postoperative dislocation in patients who underwent prior spinal fusion compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations